2013
DOI: 10.1136/bmjspcare-2013-000488
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of the Supportive and Palliative Care Indicators Tool (SPICT): a mixed-methods study

Abstract: The SPICT can support clinical judgment by multidisciplinary teams when identifying patients at risk of deteriorating and dying. It helped identify patients with multiple unmet needs who would benefit from earlier, holistic needs assessment, a review of care goals, and anticipatory care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
308
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(343 citation statements)
references
References 27 publications
(30 reference statements)
5
308
0
15
Order By: Relevance
“…Of these studies, 7 did not include outcomes data for patients who were SQ- [14][15][16][17][18][19]36 that were confirmed in the publication [15][16][17][18]36 or after contact with study authors. 14,19 In 3 studies, the SQ was used only to predict 7-and/or 30-day mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 7 did not include outcomes data for patients who were SQ- [14][15][16][17][18][19]36 that were confirmed in the publication [15][16][17][18]36 or after contact with study authors. 14,19 In 3 studies, the SQ was used only to predict 7-and/or 30-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…20 Conversely, 1 study in our review reported that the SQ no longer predicted death when included in a multivariable model with the Clinical Frailty Scale. 32 The Gold Standards Framework 5 and NECPAL 6 both use the SQ serially with general and disease-specific indicators to identify those with hospice and palliative care needs, but the Supportive and Palliative Care Indicators Tool (SPICT) 15 uses these indicators without the SQ, which was removed. Further studies will be needed to determine whether the SQ combined with other clinical indicators improves the identification of patients with hospice and palliative care needs.…”
Section: Discussionmentioning
confidence: 99%
“…The GSF Prognostic Indicator Guidance (PIG) [11,12] and the Supportive and Palliative Care Indicators Tool (SPICT) [13,14] are documents that are used internationally to assist the clinician to implement palliative care principles of pain and symptom management with psychosocial and spiritual support. At GSH and Victoria Hospital a simplified and modified 1-page tick-sheet based on the GSF-PIG is used to assist with the identification of palliative care patients (including HIV patients).…”
Section: Identifying Patients Who Require Palliative Carementioning
confidence: 99%
“…[13] The NGO sector, traditional provider of palliative care, cannot meet the total need for palliative care in SA; the government should also not expect NGOs to substitute for governmental obligations. [14] It is therefore essential that all healthcare professionals in SA are able to identify people needing palliative care, initiate basic palliative care to ensure better care in the last year of a patient's life and link such patients with community services to continue provision of palliative care in the patient's home.…”
Section: Linking With Community Resourcesmentioning
confidence: 99%
“…The Supportive and Palliative Care Indicators Tool (SPICT TM ), developed in Scotland, provides a useful approach to identifying people who may be at risk of deteriorating and therefore could benefi t from proactive palliative and supportive care. 21,22 Personalising care and decision making…”
Section: Tackling Some Of the Challenges Identifi Cationmentioning
confidence: 99%